Waning of anti-SARS-CoV-2 antibodies after the first wave of the COVID-19 pandemic in 2020: A 12-month-evaluation in three population-based European studies - Sophie Novelli; Christina Reinkemeyer; Dmitry Bulaev; Marc Paul O’Sullivan; Chantal J. Snoeck; Armin Rauschenberger; Carmelite Manto; Alexey Kolodkin; Soumyabrata Ghosh; Venkata Satagopam; Jerome le Chenadec; Karine Barthélémy; et al. (PLoS ONE, 2025)
Objectives We described waning in anti-SARS-CoV-2 IgG in adult general populations infected during the first wave of the COVID-19 pandemic in 2020 across three European countries. Methods Coordinated analyses were conducted separately in three population-based cohorts with complementary follow-up schedules: the KoCo19 (Germany), EpiCov (France), and CON-VINCE (Luxembourg) cohorts. Serological follow-up was based on the anti-SARS-CoV-2 ELISA-S IgG (Euroimmun) assay. We selected all adults aged 18–79 who had a positive serology (IgG optical density (OD) ratio ≥1.1) between February and July 2020, and at least one subsequent IgG measurement within the following 12 months, while still non-vaccinated. Results The proportion of seroreversion was 0% within the four first months, based on Koco19 data (n = 65 participants). In the longer term, 31.3% of participants had seroreverted at 6 months (95%CI: 24.4–39.1) (based on EpiCov data, n = 599), 31.3% (95%CI: 11.0–58.7) at 12 months (based on CON-VINCE data, n = 16). From EpiCov data, both baseline low IgG levels and seroneutralization negativity remained predictive of seroreversion in multivariable analysis. Conclusion From population-based cohorts, anti-S IgG levels remained stable during the first 4 months following SARS-CoV-2 infection. Most of the decay occurred afterward; nearly one-third of people seroreverted 6 and 12 months later. Low IgG levels and seroneutralization negativity were independent predictors of seroreversion.